KEBUTUHAN BELAJAR MASYARAKAT DI DESA BUMBUNG KECAMATAN MANDAU KABUPATEN BENGKALIS - Khairul Amri Amri; Daeng Ayub Natuna Ayub Natuna; Murni Baheram Baheram (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2015)
Abstract: This research aims to know the level of needs of the learning community in the Bumbung village, Mandau subdistric, Bengkalis regency. The benefits of this research are academically as a scientific paper that can improve the development of science, especially for school education in formulating the appropriate learning needs with the needs of the community. And practically is as positive input on behalf of the government in making policies and programs that can improve education and the economy in accordance with the needs of the community. Type of this research is descriptive using a quantitative which aims to give an overview about the state systematically on the objects examined. Data collection techniques in research is trough observation techniques, interview techniques, and question form. All of the statements in question form or questionnaire are presented in the form of a Likert scale is adjusted with the statement. This research is done is place in the Bumbung village, Mandau subdistric, Bengkalis regency. This research was carried out during the period from October 2014 until May 2015. The population in this research is the community ages 18-47 years of 3,973 people and for sample amounted to 199 people. Recap of the needs in terms of indicators of community learning needs learning at age 18-44 years is retrieved the value of the Mean 3,75 with SD 0,77 and categorized high or priority. Next on the whole sub indicator needs study and categories of age 18-44 year old is: a) learning needs related to religious retrieved values Mean 4.07 wih SD 0.59 and categorized very high or very priorities. 2) learning needs related to the appearance of self-accrue values Mean 4.02 with SD 0.56 and categorized very high or very priorities . 3) learning needs related to household retrieved values Mean 3.90 with SD 0.72 and categorized high or priority. 4) learning needs related to efforts in the field of agriculture obtained values Mean 3.86 with SD 0.65 and  categorized high or priority. 5) learning needs related to newly acquired knowledge of the tourism values Mean 3.74 and categorized high or priority. 6) learning needs related to the mastery of the language and general knowledge values Mean 3.67 with SD 0.85 and categorized high or priority. 7) learning needs related to job duties values Mean 3.66 with SD 0.93 and categorized high or priority. 8) learning needs associated with indulgence and recreation values Mean 3.63 with SD 0.91 and categorized high or priority. 9) learning needs relating to the services values Mean 3.17 with SD 0.89 and categorized high or priority. Key Words: Learning needs, Community.